Peranan Guru Bimbingan dan Konseling dalam Pelayanan kepada Peserta Didik pada Masa Pendemi Covid-19 di SMP N 7 Muaro Jambi - Parida Ariati (Universitas Batanghari Jambi, 2021)
Guidance and Counseling (BK) teachers should be able to become a mediator to build effective communication and pay attention to students. During the pandemic, counseling teachers can use various media and communication platforms that are familiar to students, but do not ignore the humanist value of the counselor profession. The purpose of this study was to determine the efforts of Guidance and Counseling teacher services, student responses, as well as obstacles or obstacles to Guidance and Counseling services during the COVID-19 pandemic. The research method used is descriptive phenomenology. The results of the study were that the Guidance and Counseling services provided during the COVID-19 pandemic at SMPN 7 Muaro Jambi used classical guidance services. The responses or feelings of students in the Guidance and Counseling teacher services during the COVID-19 pandemic were different for each research subject, and the obstacles or obstacles were that there were some students who did not have cellphones, insufficient costs for data packages, and networks. telephone is slow so that students become distracted in learning. Suggestions for parents should be to spend time, support, and love their children in the home environment, because children usually need the attention and support of each parent. Suggestions for the community if we have a disaster or disaster should be responded to patiently and sincerely to accept it, of course also pay attention to the regulations made by the government so that the COVID-19 pandemic can end. Suggestions for researchers for further research must be considered and prepared what is needed in research.